Aplikasi ConTrack Untuk Manjemen dan Monitoring Data Stok Barang di Perusahaan Jasa Konstruksi - Siska Mailana; Vina Ayumi (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
This research aims to develop ConTrack application, a goods and transaction management system for PT Alpha Prime Creation. The research methods used include direct observation and interviews with management and warehouse staff to identify problems in manual recording that result in input errors, recording delays, and report inconsistencies. The ConTrack application was designed using waterfall modeling. Functional testing results show that most of the main features, such as input and update of stock data, monitoring of incoming/outgoing goods, and searching for goods, work well with an average success rate of 95%. Performance testing results show that the application has an average response time of 1.2 seconds, can handle 100 active users simultaneously, and process up to 10,000 entries in less than 5 seconds. With these results, the ConTrack application is declared feasible to be applied in the operations of construction service companies as an efficient and reliable stock management support system.